Treaty for the future : the dispute settlement mechanisms of the NAFTA. - OELSTROM, Kristin L. (1994)
Highlights the major dispute settlement mechanisms incorporated in the NAFTA, and compares these mechanisms with provisions in the GATT and the US-Canada Free Trade Agreement. Analyses the provision of modifying domestic law in antidumping and countervailing duty cases, and examines the impact of this provision on the US and Mexico.